Memberi Sedekah dengan Tersembunyi: Studi Hermeneutis Terhadap Matius 6: 1-4 - Raulina, Raulina; Sitinjak, Martongo; Damanik, Erwin Syaputra; Hutahaean, Nelly Maria (CV. Creative Tugu Pena, 2020)
Giving alms is a religious practice carried out by Jews, especially by rich people. Most of them do alms by showing off their deeds to the crowd. Without ignoring the words “So let your light shine before people, so that the may see your good deeds” (Matt. 5:16), but in the text Matthew 6:1-4, Jesus commands: “Do not carry out your religious duties in front of people. People so that the can see. Alms should be given in secret. This is the focus of this research “What is the background of the problem that occurs in the context of Matthew 6:1-4 so that Jesus teaching giving alms in secret in that text? By using the critical historical interpretation method, the exploration of the meaning of the text is carried out by considering historical points of view within the text and history outside the text. The results of this research show that Jesus was not contradicting His own words. Jesus is confirming His teaching that the basis of every good deed for believers is the right motivation. Giving alms is done to realize God’s truth and justice in the world, and also for the glory of God. The importance of this research is to review the giving of alms that is intentionally published via social media today Keywords: Giving alms, Religion, Book of Matthew